Differences in Responsible Environmental Behavior based on Gender and Level of Knowledge about Waste Issues in Generation Z in Yogyakarta Province - Hanafi, Yahya; Hasanah, Uswatun; Budiaman, B (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Environmental issues related to waste are current global, national, and local. Waste is the number one priority environmental issue in DI Yogyakarta. The Generation Z group dominates the population in Indonesia and DI Yogyakarta. This study aims to analyse the differences in the REB of Gen Z based on gender, the differences in REB of Gen Z based on the level of knowledge about waste issues, and the interaction between gender and level of knowledge on REB of Gen Z. The type of research is quantitative, using a survey method. The variables used in the study are responsible environmental behaviour, knowledge about waste issues, and situational factors (gender). The data collection was carried out in January-February 2025. The research location is SMP Negeri 1 Banguntapan, Bantul, and SMA Negeri 2 Banguntapan, Bantul. The research respondents were 110 students of SMP Negeri 1 Banguntapan and 130 students of SMA Negeri 2 Banguntapan. Data analysis techniques include descriptive and inferential statistics with two-way ANOVA. The results of the hypothesis test for the gender variable are 0,052 > 0,05, so it can be concluded that there is no significant difference in gender in Gen Z REB. The hypothesis test for the variable level of knowledge about the issue of waste showed 0,00 < 0,05, and it can be concluded that there is a significant difference in the level of knowledge about the issue of waste among Gen Z REB. The hypothesis test for the interaction between the variable level of knowledge about the issue of waste and gender is 0,089 > 0,05, so it can be concluded that there is no interaction between gender and the level of knowledge about the issue of waste.